Design Thinking of Islamic Counseling Service Inspiration of Prophet’s Hadith - Firdaus, Muhammad Riyyan (Faculty of Ushuluddin UIN Sunan Gunung Djati Bandung, 2021)
This study aims to discuss the inspiration of the hadith of the Prophet in the implementation of counseling. This research method is qualitative through literature and field studies with the hadith thinking design approach. The results and discussion of this study include counseling during the pandemic, the Prophet Saw. role models in counseling, and innovations in Islamic counseling services. This research concludes that the hadith of the Prophet. has inspirational messages in a creative counseling process on Islamic counseling services through media platforms that are widely used in the contemporary era.